Extended surveillance to assess safety of 9-valent human papillomavirus vaccine. Issue 7 (30th December 2022) - Sundaram, Maria E.; Kieke, Burney A.; Hanson, Kayla E.; Belongia, Edward A.; Weintraub, Eric S.; Daley, Matthew F.; Hechter, Rulin C.; Klein, Nicola P.; Lewis, Edwin M.; Naleway, Allison L.; Nelson, Jennifer C.; Donahue, James G.
ABSTRACT: The safety of 9-valent HPV vaccine (9vHPV) has been established with regard to common and uncommon adverse events. However, investigation of rare and severe adverse events requires extended study periods to capture rare outcomes. This observational cohort study investigated the occurrence of three rare and serious adverse events following 9-valent human papillomavirus (9vHPV) vaccination compared to other vaccinations, in US individuals 9–26 years old, using electronic health record data from the Vaccine Safety Datalink (VSD). We searched for occurrences of Guillain-Barré syndrome (GBS), chronic inflammatory demyelinating polyneuropathy (CIDP), and stroke following 9vHPV vaccination from October 4, 2015, through January 2, 2021. We compared the risks of GBS, CIDP, and stroke following 9vHPV vaccination to risks of those outcomes following comparator vaccines commonly given to this age group (Td, Tdap, MenACWY, hepatitis A, and varicella vaccines) from January 1, 2007, through January 2, 2021. We observed 1.2 cases of stroke, 0.3 cases of GBS, and 0.1 cases of CIDP per 100, 000 doses of 9vHPV vaccine. After observing more than 1.8 million doses of 9vHPV, we identified no statistically significant increase in risks associated with 9vHPV vaccination for any of these adverse events, either combined or stratified by age (9–17 years of age vs. 18–26 years of age) and sex (males vs. females). Our findings provide additional evidence supporting 9vHPV vaccine safety, over longer time frames and for more serious and rare adverse events.